2000
DOI: 10.1002/1096-8652(200010)65:2<99::aid-ajh2>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Dysplastic changes in idiopathic thrombocytopenic purpura and the effect of corticosteroids to increase dysplasia and cause hyperdiploid macropolycytes

Abstract: This study evaluates the dysplastic hematological changes in nine patients with idiopathic thrombocytopenic purpura (ITP) in 11 attacks, before and after corticosteroid treatment. The pretreatment blood smears of patients with ITP, displayed more neutrophils with bizarre nuclei (P < 0.001), Döhle or Döhle-like inclusions (P < 0. 01), irregular distribution of granules (P < 0.05), hypo-agranulation (P < 0.05), pseudo-Pelger-Huet-like cells (P < 0. 01), and nuclei with chromatine clumping (P < 0.01) than the nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…The therapeutic effect of MDMP on ITP and also the hematopoetic system was known by previous reports [31][32][33][34][35][36]. It was also shown that the MDMP responsive effect on ITP is comparable with IVIG.…”
Section: Discussionmentioning
confidence: 69%
“…The therapeutic effect of MDMP on ITP and also the hematopoetic system was known by previous reports [31][32][33][34][35][36]. It was also shown that the MDMP responsive effect on ITP is comparable with IVIG.…”
Section: Discussionmentioning
confidence: 69%
“…It might be suggested that even the stem cells are affected by PVB19. Three lineage dysplasia in ITP has been reported, and may be the result of PVB19 stem cell effect [27].…”
Section: Discussionmentioning
confidence: 97%
“…Myelodysplastic changes refer to abnormal morphology of the BM and/or peripheral blood and this feature is commonly seen in MDS. Myelodysplasia in peripheral blood and BM can also be seen in different conditions such as autoimmune diseases, infections, especially viral infections, immunosuppressive drugs, chromosomal abnormalities, and DNA abnormalities [9][10][11][12][13][14][15][16][17][18][19][20]. Iron deficiency results in cellular metabolic enzyme changes, alterations in cellular growth, DNA, RNA, and protein structure, and also increased susceptibility to infections [1,2,21].…”
Section: Discussionmentioning
confidence: 99%
“…Giant platelets were not related to an associated autoimmune disease [13] or bleeding history and the patients were also examined for the presence of blood in the stool, which may cause consumption of plateles.…”
Section: Discussionmentioning
confidence: 99%